Clinical practice of nurses in the treatment of Acne (Research, Society and Development, 2022)
Acne is a common disease in adolescents, it affects the pilosebaceous follicle of the human skin, causing several factors that lead to the appearance of skin lesions characteristic of this disease. Four factors responsible for the appearance of this aesthetic dysfunction are identified, such as sebaceous hypersecretion, follicular hyperkeratinization, bacterial colonization and, consequently, underlying follicular and dermal inflammation. The aim of this study was to describe the main aesthetic treatments for acne control. This is a bibliographic review study with a descriptive and qualitative approach. There are several types of acne, but the best known is acne vulgaris. Acne can be classified into non-inflammatory acne and inflammatory acne, this classification becomes essential because it will be after it that we will determine the types of treatments to be performed. In this sense, the scientific article aims to highlight the basic principles of treatments through deep skin hygiene in adolescents and the importance of acne control in this age group. It is characterized by bibliographic research of the descriptive type with a qualitative character, based on theoretical references already published as scientific articles and books. In view of the above, we can see the importance of acne control through deep skin hygiene in adolescents, to prevent future damage to the patient's face.